Efektivitas Program Moda Angkutan Pelayanan Aman dan Nyaman Sarana Transportasi Kediri Bahagia (Mapan Satria) di Dinas Perhubungan Kota Kediri - Linda Nirmalasari; Trenda Aktiva Oktariyanda; Meirinawati Meirinawati; Eva Hany Fanida (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Mapan Satria Program represents the Kediri City Government's commitment, through the Department of Transportation, to enhance public service quality in the bus transportation sector under the name Bus Satria; however, operational obstacles such as schedule unreliability and insufficient public information persist. This study aims to describe the effectiveness of the Mapan Satria Program managed by the Kediri City Department of Transportation commencing in 2023. Program effectiveness was analyzed based on Annas's (2017) seven indicators using a qualitative method with data collection through observation, interviews, and documentation. The analysis indicates that the Mapan Satria Program (Moda Angkutan Pelayanan Aman dan Nyaman Sarana Transportasi Kediri Bahagia) has not yet operated effectively. While aspects such as timeliness, work mechanisms, inter-agency cooperation, fund disbursement, and monitoring and evaluation have been implemented in accordance with regulations, others remain suboptimal, including limited human resources, service deviations, inadequate information updates, and low public utilization. Therefore, the author recommends optimizing the program by expanding socialization to the wider community, providing clear schedule information at bus stops to facilitate passengers, strengthening the operational monitoring and evaluation system, and imposing strict sanctions for deviations.